The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1289/ehp.10168
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Residence Near Agricultural Pesticide Applications and Autism Spectrum Disorders among Children in the California Central Valley

Abstract: BackgroundAmbient levels of pesticides (“pesticide drift”) are detectable at residences near agricultural field sites.ObjectiveOur goal was to evaluate the hypothesis that maternal residence near agricultural pesticide applications during key periods of gestation could be associated with the development of autism spectrum disorders (ASD) in children.MethodsWe identified 465 children with ASD born during 1996–1998 using the California Department of Developmental Services electronic files, and matched them by ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
271
1
12

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 371 publications
(294 citation statements)
references
References 55 publications
5
271
1
12
Order By: Relevance
“…Birth prevalence is also not affected by in-migration, which may be important for studying environmental or other factors during the appropriate susceptibility period, e.g., in utero or very early in life. We have successfully used the cases in our database or the DDS file to study such factors (Roberts et al 2007;Windham et al 2006Windham et al , 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Birth prevalence is also not affected by in-migration, which may be important for studying environmental or other factors during the appropriate susceptibility period, e.g., in utero or very early in life. We have successfully used the cases in our database or the DDS file to study such factors (Roberts et al 2007;Windham et al 2006Windham et al , 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Shaw suggested that the increase in the use of acetaminophen in genetically vulnerable children, and the use of acetaminophen by pregnant women may be causal [19]. Roberts et al investigated organophosphate pesticides and suggested that women living near pesticide applications might explain the increase in ASD [20]. In 2013, Zhou et al suggested infant exposure to excess multivitamins as a potential risk factor [21].…”
Section: Potential Explanations For the Increase In Asd Prevalencementioning
confidence: 99%
“…To date, the etiology of ASD has been poorly defined; however, some studies have suggested that ASD may be caused by interactions of susceptible genes with the environment in which environmental triggers may alter gene expression (Volk et al 2014;Blake et al 2013;LaSalle 2013;Herbert et al 2006). Therefore, several investigators have examined the relationships between ASD and exposures to pesticides (Shelton et al 2012;Roberts et al 2007), ambient particulate matter (Becerra et al 2013;Volk et al 2014;Volk et al 2011), and heavy metals (Adams et al 2013;Rahbar et al 2013;Rahbar et al 2012;Shelton et al 2012;Adams et al 2007;Roberts et al 2007;Adams et al 2006;Palmer et al 2006), but results have been conflicting.…”
Section: Introductionmentioning
confidence: 99%